Herbal Prescription SH003 Alleviates Docetaxel-Induced Neuropathic Pain in C57BL/6 Mice. (11th August 2021) - Lee, Kangwook; Ku, Jin Mo; Choi, Yu-Jeong; Hwang, Hyun Ha; Jeong, Miso; Kim, Yun-Gyeong; Kim, Min Jeong; Ko, Seong-Gyu
Abstract : Docetaxel-based therapy has been applied to kill cancers including lung and breast cancers but frequently causes peripheral neuropathy such as mechanical allodynia. Lack of effective drugs for chemotherapy-induced peripheral neuropathy (CIPN) treatment leads us to find novel drugs. Here, we investigated whether and how novel anticancer herbal prescription SH003 alleviates mechanical allodynia in mouse model of docetaxel-induced neuropathic pain. Docetaxel-induced mechanical allodynia was evaluated using von Frey filaments. Nerve damage and degeneration in paw skin of mice were investigated by immunofluorescence staining. Neuroinflammation markers in bloodstream, lumbar (L4-L6) spinal cord, and sciatic nerves were examined by ELISA or western blot analysis. Docetaxel (15.277 mg/kg) was intravenously injected into the tail vein of C57BL/6 mice, and mechanical allodynia was followed up. SH003 (557.569 mg/kg) was orally administered at least 60 min before the mechanical allodynia test, and von Frey test was performed twice. Docetaxel injection induced mechanical allodynia, and SH003 administration restored withdrawal threshold. Meanwhile, degeneration of intraepidermal nerve fibers (IENF) was observed in docetaxel-treated mice, but SH003 treatment suppressed it. Moreover, docetaxel injection increased levels of TNF- α and IL-6 in plasma and expressions of phospho-NF- κ B and phospho-STAT3 in both of lumbar spinal cord and sciatic nerves, while SH003 treatment inhibited those changes. Taken together, it is worth noting that TNF- α and IL-6 in plasma and phospho-NF- κ B and phospho-STAT3 in spinal cord and sciatic nerves are putative biomarkers of docetaxel-induced peripheral neuropathy (DIPN) in mouse models. In addition, we suggest that SH003 would be beneficial for alleviation of docetaxel-induced neuropathic pain.